Respon Pengikut Terhadap Konstruksi Gender Di Tiktok :Studi Kasus Pada Akun Tiktok @Brachiokoo - Indratna, Aditya; Arindawati, Weni A.; Ramdhani, Muhamad (CV. ITTC INDONESIA, 2025)
This research aims to examine how gender construction is represented and accepted by audiences through the TikTok social media platform, with a case study of Nathania Nasywa Iskandar's @brachiokoo account. Through a qualitative approach and case study method, this research analyzes the forms of gender performativity and fluidity displayed by Nathania Nasywa Iskandar, as well as how it elicits various reactions from her followers. Data was obtained through in-depth interviews, content observation, and analysis of comments that appeared on TikTok uploads. The results showed that the content triggered complex and diverse responses, ranging from support for non-binary gender expression to moralistic and stereotypical criticism. Most followers were appreciative, especially of the way Adis packaged gender expression messages through visual and humorous approaches. However, there are also those who express confusion or even stigma towards gender identities that are considered not in accordance with prevailing social norms. This research shows the importance of social media as a new arena for negotiating identity and challenging conventional gender boundaries.